Sensory Diet Program Through In-Person and Tele-Occupationa Therapy in Children with Autism Spectrum Disorder: A Single-Blind Randomized Controlled Trial - Simin Dehghani; Marzieh Pashmdarfard; Zahra Pashazadeh Azari; Alireza Akbarzadeh Baghban; Sima Dehghani; Navid Mirzakhani Araghi (Journal of Modern Rehabilitation)
Introduction: Autism spectrum disorder (ASD) is a sensory processing, social communication, and occupational performance disorder. Sensory diets can have positive effects on these fields. Current research compared the effectiveness of the sensory diet program with and without teleoccupational therapy on sensory processing patterns, social competency and occupational performance in children with ASD. Materials and Methods: The study sample comprised 32 children with ASD 4-10 years old. They were placed in the control and intervention groups. The number of sessions for both groups was 20 30-minute sessions administered over 8 weeks. Through photos, videos, and explanations, sensory problems were described in both groups, the mother presented and implemented activities and environmental adaptations, and the therapist supervised the implementation. This study used three tools—sensory profile 2, social responsive scale 2 and Canadian occupational performance measure. Results: According to the sensory profile 2, social responsiveness scale, and Canadian occupational performance measure, processing in the areas of auditory, visual, touch, movement, body position, oral, conduct, social-emotional, attentional, sensory seeking, sensory avoiding, sensory sensitive, low registration, social awareness, social cognition, social communication, social motivation, limited interests, repetitive behaviors, and occupational performance in both groups have a significant difference (P<0.05). Conclusion: It seems that providing a sensory diet program through teleoccupational therapy on sensory processing patterns, social competency, and occupational performance is applicable, as well as face-to-face occupational therapy in children with ASD.